2020
DOI: 10.1021/acs.nanolett.0c02595
|View full text |Cite
|
Sign up to set email alerts
|

Building Fast Diffusion Channel by Constructing Metal Sulfide/Metal Selenide Heterostructures for High-Performance Sodium Ion Batteries Anode

Abstract: Heterostructure engineering is one of the most promising modification strategies toward improving sluggish kinetics for the anode of sodium ion batteries (SIBs). Herein, we report a systemic investigation on the different types of heterostructure interfaces’ effects of discharging products (Na2O, Na2S, Na2Se) on the rate performance. First-principle calculations reveal that the Na2S/Na2Se interface possesses the lowest diffusion energy barrier (0.39 eV) of Na among three kinds of interface structures (Na2O/Na2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(101 citation statements)
references
References 41 publications
0
101
0
Order By: Relevance
“…The high‐resolution Sn 3d spectrum in Figure 2b is fitted by two obvious peaks located at 485.9 eV (Sn 3d 5/2 ) and 494.3 eV (Sn 3d 3/2 ), which correspond to Sn 2+ in the SnSe bonding states. [ 17,22 ] The small peaks at 484.4 and 492.9 eV at lower binding energies can be assigned to Sn 2+ in the SnS bonding states. [ 17,23 ] The Se 3d spectrum in Figure 2c exhibits two obvious peaks at 53.5 eV (Se 3d 5/2 ) and 54.7 eV (Se 3d 3/2 ), which indicates the presence of SnSe bonding states.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high‐resolution Sn 3d spectrum in Figure 2b is fitted by two obvious peaks located at 485.9 eV (Sn 3d 5/2 ) and 494.3 eV (Sn 3d 3/2 ), which correspond to Sn 2+ in the SnSe bonding states. [ 17,22 ] The small peaks at 484.4 and 492.9 eV at lower binding energies can be assigned to Sn 2+ in the SnS bonding states. [ 17,23 ] The Se 3d spectrum in Figure 2c exhibits two obvious peaks at 53.5 eV (Se 3d 5/2 ) and 54.7 eV (Se 3d 3/2 ), which indicates the presence of SnSe bonding states.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17,22 ] The small peaks at 484.4 and 492.9 eV at lower binding energies can be assigned to Sn 2+ in the SnS bonding states. [ 17,23 ] The Se 3d spectrum in Figure 2c exhibits two obvious peaks at 53.5 eV (Se 3d 5/2 ) and 54.7 eV (Se 3d 3/2 ), which indicates the presence of SnSe bonding states. [ 24 ] In addition, the broad peak at 58.1 eV corresponds to the SeO bond, which is related to the tin selenite phase formed by the surface oxidization of tin selenide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[64,[86][87][88][89][90] Furthermore, it has been reported that the presence of different materials during galvanostatic charge and discharge processes helps alleviate the volume change of the electrode materials because the compounds undergo electrochemical processes at different potentials; materials that are inactive at a certain potential help release the strain received by the other material, and consequently, the cycle life of the electrodes can be prolonged. [55,61,83] To understand the effects of heterointerfaces on enhancing the electrochemical properties, a combination of theoretical calculations and experimental methods is widely used, which is discussed in the section below.…”
Section: Theoretical and Experimental Understanding Of Heterostructure Effects And Analytical Tools For Identification Of Components In Hmentioning
confidence: 99%
“…For example, SnS/SnSe 2 heterostructured electrode reported by Wang et al goes through multi-step electrochemical reactions during discharge and charge process. [55] During discharge, SnSe 2 firstly goes through conversion process to yield metallic Sn as well as Li 2 Se, and SnS is decomposed at lower potential. Since nanosized Sn regions are in contact with SnS phase, flow of electrons occurs from metallic Sn to SnS, which also facilitates the electrochemical kinetics.…”
Section: Introductionmentioning
confidence: 99%